Pushing the limits: an instrument for hard X‐ray imaging below 20 nm. (3rd February 2015) - Nazaretski, E.; Lauer, K.; Yan, H.; Bouet, N.; Zhou, J.; Conley, R.; Huang, X.; Xu, W.; Lu, M.; Gofron, K.; Kalbfleisch, S.; Wagner, U.; et al.
<x xml:space="preserve">Abstract</x> Hard X‐ray microscopy is a prominent tool suitable for nanoscale‐resolution non‐destructive imaging of various materials used in different areas of science and technology. With an ongoing effort to push the 2D/3D imaging resolution down to 10 nm in the hard X‐ray regime, both the fabrication of nano‐focusing optics and the stability of the microscope using those optics become extremely challenging. In this work a microscopy system designed and constructed to accommodate multilayer Laue lenses as nanofocusing optics is presented. The developed apparatus has been thoroughly characterized in terms of resolution and stability followed by imaging experiments at a synchrotron facility. Drift rates of ∼2 nm h−1 accompanied by 13 nm × 33 nm imaging resolution at 11.8 keV are reported.